PENINGKATAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN PICTURE AND PICTURE PADA MATA PELAJARAN PPKN KELAS III DI MI AL MUNAWAROH BOGOR - Willa Putri; Siti Aisah; Yoyoh Rabiatul Adawiyah (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2023)
The low student learning outcomes that can often be found in elementary schools are still a problem that often occurs. Requires an interactive learning model that must be used by teachers so that student learning outcomes can increase. The purpose of this study was to determine the improvement of learning outcomes in Pancasila and Citizenship Education learning at MI Al Munawaroh Bogor trought the application of the Picture and Picture learning model. This type of research is classroom Action Research which is carried out in two cycles. This research was applied to third grade students who opened 31 people with four stages, namely the planning stage, implementation stage, observation, interviews, and documentation. The Results showed an increase in student learning activity in learning Pancasila and Citizenship Education through the Picture and Picture model. The data obtained in the first cycle of student learning outcomes are in the medium category and the second cycle is in the high category. Student learning outcomes are also reflected through increased student activity, attention and focus on teaching materials, and participation in questions and answer.